Where Are the Women? An Analysis of Gender Mainstreaming in Introductory Political Science Textbooks. Issue 2 (3rd April 2017) - Atchison, Amy L.
ABSTRACT: Textbook content is a powerful indicator of what is and is not considered important in a given discipline. Textbooks shape both curriculum and students' thinking about a subject. The extant literature indicates that gender is not well represented in American government textbooks, thus signaling to students that women and gender are not part of the mainstream in political science. I contribute to this literature by using quantitative and qualitative content analysis to examine gender mainstreaming in 10 introductory political science textbooks. I find that the quantity of gendered content is small, and the quality of that content varies considerably from text to text.